Obstetrician–gynecologists’ counseling regarding postpartum sterilization - Arora KS; Castleberry N; Schulkin J (Dove Medical Press, 2018)
Kavita Shah Arora,1 Neko Castleberry,2 Jay Schulkin2,3 1Department of Obstetrics and Gynecology, MetroHealth Medical Center, Case Western Reserve University, Cleveland, OH, USA; 2Research Department, The American College of Obstetricians and Gynecologists, Washington, DC, USA; 3Department of Obstetrics and Gynecology, University of Washington, School of Medicine, Seattle, WA, USA Introduction: Obstetrician–gynecologists (ob-gyns) play a prominent role in counseling patients regarding sterilization, offering alternative contraception, fulfilling sterilization requests, and referring patients if unable to provide the service due to a personal moral belief. Therefore, we sought to better characterize the counseling practices of ob-gyns with respect to postpartum sterilization. Materials and methods: This is a prospective, electronic survey-based study of 1,000 ob-gyn members of the American College of Obstetricians and Gynecologists, half of whom are members of the Collaborative Ambulatory Research Network. Results: A total of 188 of 957 surveyed physicians (19.6%) opened and responded to the survey, after accounting for exclusions. Age (31.9%), body mass index (28.7%), and medical history (27.1%) were the three most frequent reasons for an ob-gyn reported declining to perform sterilization in a patient requesting sterilization. Medical history (36.2%), parity (31.9%), and availability of alternative contraception (27.7%) were the three most frequent reasons that an ob-gyn reported recommending postpartum sterilization in a patient not requesting sterilization. Conclusion: Our study has identified both medical and nonmedical factors that impact ob-gyns likelihood to recommend either toward or against postpartum sterilization. Nonmedical factors included clinical logistical issues such as availability of the operating room as well as considerations of a patient’s age, parity, gestational age at delivery, and whether the husband was in agreement. Physicians should be cautious of inappropriately blending medical decision-making with paternalistic counseling. Keywords: postpartum sterilization, contraception, counseling, patient–physician relationship, bias